Ultrastructural Interrelationship between the Pineal Gland and the Testis in the Male Rat - Kuş, İlter; Sarsılmaz, Mustafa; Ögetürk, Murat; Yılmaz, Bayram; Keleştimur, Haluk; Öner, Hakan (My University, 2000)
The ultrastructural interrelationship between the pineal gland and testis was evaluated in the rat. Wistar rats were divided into 6 groups. Groups I and II were sham-orchidectomized and orchidectomized rats, respectively. Rats in group III were orchidectomized and daily injected with testosterone propionate (TP) for 1 month. Groups IV and V were sham-pinealectomized and pinealectomized, respectively. Group VI was pinealectomized and daily injected with melatonin for 2 months. All animals were anesthetized with ketamine for fixation by vascular perfusion. Pineal glands of groups I, II, and III and the testes of groups IV, V, and VI were removed and weighed. All specimens were examined by electron microscopy. Orchidectomy caused an increase of lipid droplets, cytoplasmic dense bodies, and lysosomes. Rough endoplasmic reticulum, Golgi apparatus, and mitochondria were extensive in the cytoplasm. TP administration to orchidectomized rats resulted in formation of less extensive lipid droplets and mitochondria. In pinealectomized rats, golgi complex, mitochondria, and enlarged smooth endoplasmic reticulum were extensive in the cytoplasm of Leydig cells. Formation of cytoplasmic secretory granules and osmiophilic bodies was observed. Testicular weight increased compared to group IV. Melatonin decreased testicular weight in comparison to group V and prevented ultrastructural changes. Pinealectomy and orchidectomy caused hyperactivity in Leydig cells and pinealocytes, respectively, which suggests a mutual relationship between the pineal gland and testis in the rat.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Leydig cell; melatonin; pinealocyte; testosterone; electron microscopy